2019
DOI: 10.29303/jipp.v3i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Code Switching In Classroom Discourse: A Sociolinguistic Study

Abstract: This research attempts to find out the most frequently used type and the function of codeswitching, also the implication of code-switching towards the teaching and learning situation in two classrooms of the fourth semester at English Education Department, University of Mataram. The descriptive qualitative method was adopted in conducting this method. The data collection was done through observation, recording and interview. The results of this study showed that three are types of code-switching are found in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The other example of code-switching is done from English to Arabic sometimes. It refers to the translation required by the students to understand the sentence's meaning (Yulandari et al, 2018). It is conducted by considering the language used to facilitate the students to have expanded knowledge about language and to make it grow together.…”
Section: A) Knowledge Construction/curriculum Accessmentioning
confidence: 99%
See 4 more Smart Citations
“…The other example of code-switching is done from English to Arabic sometimes. It refers to the translation required by the students to understand the sentence's meaning (Yulandari et al, 2018). It is conducted by considering the language used to facilitate the students to have expanded knowledge about language and to make it grow together.…”
Section: A) Knowledge Construction/curriculum Accessmentioning
confidence: 99%
“…The use of Code-switching in the classroom is to preserve interpersonal relationships between teachers and students and humanize the classroom such as joking, humor, giving motivation, and praise to reduce students' anxiety. This function is to construct a supportive classroom climate and to appreciate the students as human (Rolin-Ianziti & Brownlie, 2002;Yulandari et al, 2018). According to Cahyani et al, (2018), they reported where teachers of tertiary level in Indonesian context found that teachers commonly gave praise in English because they thought English is expressive with various forms of utterances.…”
Section: C) Interpersonal Relationmentioning
confidence: 99%
See 3 more Smart Citations